Neural responses to monetary incentives in postpartum women affected by baby blues. (February 2023) - Chechko, Natalia; Stickel, Susanne; Votinov, Mikhail
Abstract: Up to 50% of new mothers experience baby blues (BB) within a week of delivery, with affective disturbances being the central symptoms. Because reward processing is known to be affected in depression, this study sought to investigate whether incentive processing during the experience of BB can be altered through the monetary incentive delay (MID) task. The MID task allows reward processing to be investigated based on responses to 'anticipation' and 'feedback of reward or loss'. 60 women participated in the fMRI-based MID task within 1–6 days of delivery, and 50% of them developed BB within the first few postpartum weeks. Over a 12-week observation period, a greater number of women in the BB group (52% vs. 13%) developed psychiatric conditions, with 24% of women with BB developing postpartum depression compared to only 3% of those without BB. During the feedback trials of the MID task, women with BB, compared to those without, showed increased activation in both the winning and losing trials (the temporal areas, the insula, the midbrain, and the inferior frontal gyrus). During the anticipation trials, however, subjects affected by BB showed reduced activation in the pregenual and the subgenual anterior cingulate cortices (pg/sg ACC). Our results demonstrate, for the first time, that the BB-related time window overlaps with alterations in the brain networks associated with incentive processing. Given the involvement of pg/sgACC in the development of depressive mood, the weaker involvement of these brain regions during anticipation in participants affected by BB is of particular interest. Highlights: Up to 50% of new mothers experience 'baby blues' as a response to a hormone deficiency after delivery. Baby blues is a risk factor for the development of a postpartum affective disorder. A weaker involvement of the subgenual prefrontal cortex during reward anticipation is observed. Neural circuit dysfunctions in the reward system may contribute to baby blues symptoms.